Positive correlation between size at initiation of chromosome replication in Escherichia coli and size at initiation of cell constriction. - Koppes, L J (1980)
The variability of (i) the length (size) at which cells initiate chromosome replication, (ii) the length at which they initiate cell constriction, and (iii) the time interval between these events has been estimated for Escherichia coli B/r K at two different slow growth rates. Steady-state cultures were pulse-labeled with [3H]thymidine and, after fixation, analyzed by electron microscopic radioautography. The coefficient of variation of length at initiation of chromosome replication was found to be 15 to 22%, the coefficient of variation of length at initiation of cell constriction was 10%, and the coefficient of variation of the time interval between both events was 25%. With the help of these values we calculated a high positive coefficient of correlation (rho) between the length at which a round of chromosome replication is initiated and that at which the onset of cell constriction occurs. At both growth rates rho has a value of 0.6 to 1.0. This correlation excludes a model in which chromosome initiation and cell constriction are independently triggered by some aspects of cell growth. It favors a model in which an event before or at chromosome initiation triggers both.